Teaching Assessment: Preparing our Colleagues Through Graduate Education. Issue 177 (9th October 2018) - Ballysingh, Tracy Arámbula; Hernández, Ignacio; Zerquera, Desiree
Abstract: This chapter provides a framework for grounding social justice principles at the center of learning in higher education program assessment and evaluation courses. Pedagogical reflections are drawn from the classroom experiences of three faculty of color who represent diverse institutional, programmatic, and geographic contexts. Their advanced framework incorporates theories of experiential learning, critical pedagogy, and problems of practice. It further explains how these notions might converge to foster a social justice‐centered approach to graduate instruction of assessment and evaluation for higher education and student affairs. The authors incorporate excerpts from course syllabi and lesson plans to demonstrate how this framework better integrates social justice principles with the practice of assessment; two concepts commonly treated as separate pedagogical entities. This chapter will inform faculty in higher education and student affairs graduate programs, institutional researchers, and practitioners committed to advancing assessment practices that embrace social justice as a core value in higher education.